2008
DOI: 10.1111/j.1600-065x.2008.00606.x
|View full text |Cite
|
Sign up to set email alerts
|

Signaling defects in anti‐tumor T cells

Abstract: The immune response to cancer has been long recognized, including both innate and adaptive responses, showing that the immune system can recognize protein products of genetic and epigenetic changes in transformed cells. The accumulation of antigen-specific T cells within the tumor, the draining lymph node, and the circulation, either in newly diagnosed patients or resultant from experimental immunotherapy, proves that tumors produce antigens and that priming occurs. Unfortunately, just as obviously, tumors gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 147 publications
1
64
0
Order By: Relevance
“…While many studies have improved our understanding of tumor initiation and progression, many questions regarding the phenomenon of an increasingly ineffective tumor immune response during tumor growth are in need of elucidation [5,6] . In fact, during cancer progression colorectal tumor cells acquire various characteristics that allow them to evade immunological surveillance [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…While many studies have improved our understanding of tumor initiation and progression, many questions regarding the phenomenon of an increasingly ineffective tumor immune response during tumor growth are in need of elucidation [5,6] . In fact, during cancer progression colorectal tumor cells acquire various characteristics that allow them to evade immunological surveillance [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Because ganglioside inhibition of immune cell function is often reversible, inhibition of lytic activity in CTL by shed gangliosides might be reversed by removal of CTL from the tumor ganglioside-rich tumor microenvironment. This would provide an explanation for the rapid recovery of tumor-specific cytotoxic activity of CD8 + tumor-infiltrating lymphocytes upon in vitro culture after isolation from the tumor mass (3,42).…”
Section: Discussionmentioning
confidence: 98%
“…Lytic activity of CD8 + CTL has been shown to be defective in various mouse tumor models and in human cancer (3). Soluble factors generated as a result of tumor growth (i.e., produced by tumor and/or by host [immune] cells) have been proposed to have an important role in inhibiting CD8 + T cell lytic function.…”
Section: Ytotoxic T Lymphocytes Are a Critical Component Of Adaptivmentioning
confidence: 99%
“…For instance, it was shown that tumorspecific T cells from the peripheral blood of cancer patients exert potent responses in vitro, but T cells isolated from the tumor tissue were rather unresponsive [77]. T cells exposed to chronic antigen stimulation, such as during viral infection and cancer progression, became functionally impaired and displayed an exhausted phenotype [78].…”
Section: Shaping Of Nk Cell Function By the Tumor Microenvironmentmentioning
confidence: 99%
“…In addition to the increased expression of inhibitory receptors, the impairment of T cell responses in the tumor tissue is characterized by changes in the signaling machinery of the TCR complex [77]. These include decreased expression of the adaptor molecule CD3ζ, tyrosine kinases Lck and Fyn and reduced expression of NF-κB family members that were correlated with impaired cytokine production by cytotoxic T lymphocytes.…”
Section: Shaping Of Nk Cell Function By the Tumor Microenvironmentmentioning
confidence: 99%